E EVALUASI PROGRAM KELAS UNGGULAN DALAM MENINGKATKAN MUTU PENDIDIKAN MENGGUNAKAN MODEL EVALUASI KONTEKS, INPUT, PROSES, DAN PRODUK - Mohamad, Mohamad Ibadi; Syarwani, Syarwani Ahmad; Destiniar, Destiniar (EduTeach : Jurnal Edukasi dan Teknologi Pembelajaran, 2025)
The excellent class program is an alternative strategy to improve the quality of education by providing more intensive and quality learning for high-achieving students. This study aims to show the effectiveness of the excellent class program in improving the quality of education by evaluating the Context, Input, Process, and Product models. The location of the study was SMA Negeri 3 Palembang. The method used in the study was qualitative with a phenomenological approach. Data were collected through observation, interviews, and documentation. The results of the study showed that the excellent class facilitated outstanding students to develop optimally. This program has a positive impact on improving the quality of education, seen from student academic achievement, learning motivation, and character and skill development. The school has succeeded in improving the quality of graduates with 80% continuing their higher education. However, there are still obstacles to facilities, disruptions between students in excellent classes and regular classes, and teacher-parent relationships. Therefore, improvements are needed to be more optimal and sustainable.